Inborn Errors of Immunity and Their Phenocopies: CTLA4 and PD-1 - Hao, Yuwei; Cook, Matthew C. (Frontiers in Immunology, 2022)
Elucidating links between genotype and phenotype in patients with rare inborn errors of immunity (IEIs) provides insights into mechanisms of immune regulation. In many autosomal dominant IEIs however, variation in expressivity and penetrance result in complex genotype-phenotype relations, while some autosomal recessive IEIs are so rare that it is difficult to draw firm conclusions. Phenocopies arise when an environmental or non-genetic factor replicates a phenotype conferred by a specific genotype. Phenocopies can result from therapeutic antibodies or autoantibodies that target a protein to replicate aspects of the phenotype conferred by mutations in the gene encoding the same protein. Here, we consider IEIs arising from rare genetic variants in CTLA4 and PDCD1 and compare clinical and laboratory manifestations arising as drug-induced phenocopies (immune related adverse events, IRAEs) in cancer patients treated with immune checkpoint inhibitors (ICI) to illuminate genotype-phenotype relations of IEIs and identify outstanding questions regarding mechanism of disease.